Identification of the Prognostic Signatures of Glioma With Different PTEN Status - Zhang, Pei; Meng, Xinyi; Liu, Liqun; Li, Shengzhen; Li, Yang; Ali, Sakhawat; Li, Shanhu; Xiong, Jichuan; Liu, Xuefeng; Li, Shouwei; Xia, Qin; Dong, Lei (Frontiers in Oncology, 2021)
The higher-grade glioma is characterized by cell heterogeneity and gene mutations and companies with a poor prognosis. The deletions and mutations of the tumor suppressor gene PTEN (5%-40%) in glioma patients are associated with worse survival and therapeutic resistance. Characterization of molecular signatures caused by PTEN status is the key to predict the prognosis of glioma. This study established the novel risk model, screened optimal prognostic signatures and calculated the risk score for the individual glioma patient with different PTEN status. Our result shows that fourteen and three independent prognostic gene signatures in PTEN-wt and PTEN-mut subgroup, respectively. We also verified that the risk score is an independent prognostic factor, significantly correlated with tumor malignancy. Due to the higher malignancy of the PTEN-mut glioma, we explored potential therapy targeting the independent prognostic signatures in PTEN-mut glioma (CLCF1, AEBP1 and OS9). Notably, the small molecule compound (+)-JQ1 could bind to all three proteins, indicating a potential therapy for PTEN-mut glioma. In sum, gene signatures and risk scores in our risk model are helpful for glioma diagnosis, prognosis prediction and treatment.